Modeling and Simulation of Single Phase AC Motor Using First and Second Order Transfer Functions - Mohamad Sufyan Tegar Pratama (Journal of Marine Electrical and Electronic Technology, 2025)
Single phase AC motors are widely used in household and light industrial drive systems due to their simple structure and cost effectiveness. However, in the context of precision control, the mathematical modeling of single phase AC motors is often oversimplified, resulting in transfer functions that do not accurately reflect their true electromechanical characteristics. This study aims to develop and compare first and second order transfer functions of a 0.18 kW WEG W22 single phase AC motor to analyze model accuracy in representing system dynamics. The main contribution of this research is the formulation of transfer functions based on real technical parameters from the datasheet, followed by performance evaluation through MATLAB/Simulink simulation. The modeling process involves deriving the first order model from a linear mechanical system and the second order model from a comprehensive electromechanical approach. The simulation results indicate that the second order model provides a faster and more stable system response, offering better alignment with the actual behavior of the motor under dynamic conditions. In conclusion, the second order transfer function presents a more accurate dynamic representation of the single phase AC motor and is suitable as a foundation for precision control system design.